Design of Information Systems Sale of Goods in CV. Loka Karya Sidoarjo - Yudhistira Eka Wishnu Putra; Henry Bambang Setyawan; Ignatius Adrian Mastan (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Sales transactions is a major transaction on the CV. Loka Karya Sidoarjo, poor existing system can make the process these transactions into long and lead to additional costs, and can reduce the profits derived by an enterprise. Many companies are still using Microsoft Office Exel as the main database of the various transactions that exist, so companies get very limited information to be used as reference for future decision making.The solution to overcome these problems is to create an information system able to manage the sale of goods that all transactions in the company accurately, quickly and easily with a desktop base. Based on trial results information system that has been done with CV. Loka Karya hence the presence of these can provide a CV. Loka Karya in the data management process of selling goods to generate reports or accurate information, helping companies in the goods receipt data management and overcome bad credit problems. All the features available in this program can make the company into increased productivity and mitigate the risks that occur.